Strengthening digital citizenship through discourse analysis of presidential and vice-presidential candidates in the 2024 Presidential Election - Mulyono, Budi; Trilatifah, Winda; Nasichuddin, Moch. Ari; Syambudi, Irwan; Trisnawati, Diana (Universitas Negeri Yogyakarta, 2024)
With the rapid advancement of information technology and increased internet access in Indonesia, citizens' participation in the digital realm has grown substantially. Digital citizens' presence is crucial in the 2024 Presidential Election, playing a pivotal role in disseminating political information, influencing public opinion, and providing support to candidates. This study examines the digital citizens' discourse on presidential and vice-presidential candidate pairs in the 2024 election in the digital public sphere. The method of issue analysis employs topic modeling with keywords